Trends in Diabetes-Related Potentially Preventable Hospitalizations in Adult Population in Spain, 1997–2015: A Nation-Wide Population-Based Study - Gómez-Huelgas, Ricardo (J Clin Med, 2019)
We aimed to assess national trends in the rates of diabetes-related potentially preventable hospitalizations (overall and by preventable condition) in the total adult population of Spain. We performed a population-based study of all adult patients with diabetes who were hospitalized from 1997 to 2015. Overall potentially preventable hospitalizations and hospitalizations by diabetes-related preventable conditions (short-term complications, long-term complications, uncontrolled diabetes, and lower-extremity amputations) were examined. Annual rates adjusted for age and sex were analyzed and trends were calculated. Over 19-years-period, 424,874 diabetes-related potentially preventable hospitalizations were recorded. Overall diabetes-related potentially preventable hospitalizations decreased significantly, with an average annual percentage change of 5.1 (95%CI: −5.6–(−4.7%); p(trend) < 0.001). Among preventable conditions, the greatest decrease was observed in uncontrolled diabetes (−5.6%; 95%CI: −6.7–(−4.7%); p(trend) < 0.001), followed by short-term complications (−5.4%; 95%CI: −6.1–(−4.9%); p(trend) < 0.001), long-term complications (−4.6%; 95%CI: −5.1–(−3.9%); p(trend) < 0.001), and lower-extremity amputations (−1.9%; 95%CI: −3.0–(−1.3%); p(trend) < 0.001). These reductions were observed in all age strata for overall DM-related PPH and by preventable condition but lower-extremity amputations for those <65 years old. There was a greater reduction in overall DM-related PPH, uncontrolled DM, long-term-complications, and lower extremity amputations in females than in males (all p < 0.01). No significant difference was shown for short-term complications (p = 0.101). Our study shows a significant reduction in national trends for diabetes-related potentially preventable hospitalizations in Spain. These findings could suggest a sustained improvement in diabetes care in Spain, despite the burden of these diabetes-related complications and the increase in the diabetes mellitus prevalence.